Analysis of resilience and academic performance among university students (National Administration Journal, 2021)
Resilience has taken a leading role in various areas, from the psychological to the business aspect. The objective is to determine the relationship between the resilient protective factors with the academic performance of college students. The Wagnild & Young (1993) instrument was applied, achieving a reliability of Cronbach's Alpha of 0.91. The sample size was 497 students. Self-confidence and perseverance were determined as strengths, while the weaknesses were: personal satisfaction, equanimity and feeling well alone. it was determined that resilience does not significantly explain academic performance.
Keywords: Resilience; protective factors; risk factors; academic success